2009
DOI: 10.1016/j.jacc.2009.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Dose Modified-Release Nicotinic Acid on Atherosclerosis and Vascular Function

Abstract: In statin-treated patients with low HDL-C, high-dose modified-release NA, compared with placebo, significantly reduces carotid atherosclerosis within 12 months. (Oxford Niaspan Study: Effects of Niaspan on Atherosclerosis and Endothelial Function; NCT00232531).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(116 citation statements)
references
References 50 publications
1
112
0
3
Order By: Relevance
“…In patients with CAD, the addition of niacin significantly improved endothelial function in patients with low HDLcholesterol levels [217,218]. In statin-treated patients with low HDL-cholesterol and CVD (65% T2D with CAD), 12 months of niacin treatment, when compared with placebo, significantly reduced carotid atherosclerosis, but did not alter either aortic distensibility or brachial artery FMD [219]. Statin-treated T2D with LDL-cholesterol <2.5mmol/L and ED were randomized to niacin (nicotinic acid prolonged release) or no additional therapy [220].…”
Section: Combination Therapiesmentioning
confidence: 97%
“…In patients with CAD, the addition of niacin significantly improved endothelial function in patients with low HDLcholesterol levels [217,218]. In statin-treated patients with low HDL-cholesterol and CVD (65% T2D with CAD), 12 months of niacin treatment, when compared with placebo, significantly reduced carotid atherosclerosis, but did not alter either aortic distensibility or brachial artery FMD [219]. Statin-treated T2D with LDL-cholesterol <2.5mmol/L and ED were randomized to niacin (nicotinic acid prolonged release) or no additional therapy [220].…”
Section: Combination Therapiesmentioning
confidence: 97%
“…However, a recent study clearly showed that HDL isolated from subjects with T2DM after 3 months of treatment with niacin displayed an improved ability to stimulate NO production, to reduce reactive oxygen species, and to promote EPC-mediated endothelial repair in vitro when compared to HDL isolated at baseline (Sorrentino et al 2010), further strengthening the concept that plasma HDL-C and its change may not be a reliable indicator of HDL function. Recent studies analyzed the effect of niacin treatment in patients with established CAD on top of the existing statin therapy; two of them failed to detect any significant improvement of FMD, while in one case FMD was significantly increased only in the subgroup of patients with a low baseline HDL-C level (Lee et al 2009;Philpott et al 2013;Warnholtz et al 2009). …”
Section: Niacinmentioning
confidence: 99%
“…Magnetic resonance imaging enables characterization of plaque burden and composition, with early studies reporting the favorable effects of statins 82 and niacin. 83 However, this technique is limited to imaging larger arteries and at this point in time evaluation of the effect of novel therapies on coronary atherosclerosis is not possible. The ability to combine these non-invasive techniques with molecular targeted agents will enable study of the effects of therapies on specific factors in atherosclerotic plaque that is involved in rupture.…”
Section: Non-invasive Imagingmentioning
confidence: 99%